Origin of Local Structures of U-Co Melts: A First-Principles Study - Zhang, Huanqing; Sun, Honggang; Li, Qiutong; Wang, Li (Frontiers in Materials, 2022)
The local structures of U-Co melts have been studied by first-principle calculations. Two sub-peaks are observed in the first peaks of U-U pair distribution functions. The Voronoi polyhedral analyses also show two separate core-shell U-U distances. Therefore, the calculated results propose that U atoms will play dual roles, “chemical” and “topological”, in the local structures of U-Co melts. In addition, the chemical effect of U atoms will be strengthened when containing more U atoms. The interaction of Co and U atoms is slightly affected by the compositions. The Co-centered clusters are mostly prism-like or antiprism-like polyhedral, which can be predicted by the solute-solvent model. The distribution of the coordinated numbers of Co atoms is much narrower than that of U atoms, showing relatively stable Co-centered clusters. The chemical and topological roles of U atoms are intuitively observed in the electron density of U-Co melts, which presents both metallic and covalent bonding characteristics for U-U bonds. In the end, we conclude that the partial localization of U 5f-electron is responsible for the dual roles of U atoms. The present results provide a theoretical understanding of the origin of the local structures of U-Co melts.